2006
DOI: 10.1007/s00264-005-0045-z
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic protein-1 (BMP-7) accelerates healing of scaphoid non-union with proximal pole sclerosis

Abstract: We randomly assigned 17 patients with scaphoid non-union at the proximal pole to three treatment groups: (1) autologous iliac graft (n=6), (2) autologous iliac graft + osteogenic protein-1 (OP-1; n=6), and (3) allogenic iliac graft + OP-1 (n=5). Radiographic, scintigraphic, and clinical assessments were performed throughout the follow-up period of 24 months. OP-1 improved the performance of both autologous and allogenic bone implants and reduced radiographic healing time to 4 weeks compared with 9 weeks in gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 23 publications
0
69
0
5
Order By: Relevance
“…They have been tested in various experimental animal nonunion models [32,39]. Since the FDA approval of BMP-7 for the treatment of recalcitrant tibial nonunions in 2001, its efficacy has been verified in a number of randomized trials [5,18,27] and large clinical series [12,15,23,26,33,38] with healing rates ranging from 81% to 92%.…”
Section: Introductionmentioning
confidence: 99%
“…They have been tested in various experimental animal nonunion models [32,39]. Since the FDA approval of BMP-7 for the treatment of recalcitrant tibial nonunions in 2001, its efficacy has been verified in a number of randomized trials [5,18,27] and large clinical series [12,15,23,26,33,38] with healing rates ranging from 81% to 92%.…”
Section: Introductionmentioning
confidence: 99%
“…Bone morphogenetic proteins (BMP) are potent local factors that have been shown to have specific functions during organogenesis and embryogenesis, regulate the differentiation of mesenchymal progenitor cells, and promote bone and cartilage formation in bone and cartilage defects, fracture repair, and periodontal diseases [3,5,11,[15][16][17]. BMPs are members of the transforming growth factor-β (TGF-β) superfamily and were first identified by their ability to induce ectopic bone formation in vivo [11].…”
Section: Introductionmentioning
confidence: 99%
“…Injection of growth factors is based on the tremendous effect that these molecules exert to induce upregulation of bone healing [91]. Currently, a variety of molecules including BMP-2, BMP-7, platelet-derived growth factor, fibroblast derived growth factor and PTH have been used for the treatment of nonunions in experimental studies (animal models) [4,7,8,50,67,71,77,95,97,100,114]. The results have shown that the molecules are capable of upregulating the healing process, thus accelerating the fracture consolidation and mechanical properties [50, 71,77,89,95,100,114].…”
Section: Discussionmentioning
confidence: 99%
“…Autologous cancellous bone grafting (ABG) remains the gold standard biological method used to promote bone healing by stimulating the local micro-environment at the nonunion site [7,9,34,35,87,101]. However, its limited availability, as well as the donor site morbidity and complications such as chronic pain, neurovascular injury and infection have dictated the need for the development of alternative methods of biological stimulation [3,15,17,24,34,35,39,49,96,105,112].…”
Section: Introductionmentioning
confidence: 99%